2019
DOI: 10.1634/theoncologist.2019-0382
|View full text |Cite
|
Sign up to set email alerts
|

Oral Care Evaluation to Prevent Oral Mucositis in Estrogen Receptor-Positive Metastatic Breast Cancer Patients Treated with Everolimus (Oral Care-BC): A Randomized Controlled Phase III Trial

Abstract: Background The incidence of oral mucositis (any grade) after everolimus treatment is 58% in the general population and 81% in Asian patients. This study hypothesized that professional oral care (POC) before everolimus treatment could reduce the incidence of everolimus‐induced oral mucositis. Materials and Methods This randomized, multicenter, open‐label, phase III study evaluated the efficacy of POC in preventing everolimus‐induced mucositis. Patients were randomized into POC and control groups (1:1 ratio) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…The Oral Care-BC trial showed that POC is effective in suppressing oral mucositis in breast cancer patients receiving everolims and exemestane therapy [16]. Oral care is a method that can be easily administered globally and should be considered a new standard before administering these drugs, especially in the rst 8 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Oral Care-BC trial showed that POC is effective in suppressing oral mucositis in breast cancer patients receiving everolims and exemestane therapy [16]. Oral care is a method that can be easily administered globally and should be considered a new standard before administering these drugs, especially in the rst 8 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of the study protocol and treatment in the Oral Care-BC trial Oral Care-BC is a Japan-based, phase 3, multicenter randomized clinical trial that assessed the effectiveness of POC in preventing oral mucositis in patients treated with everolimus and exemestane for hormone receptor-positive, human epidermal growth factor receptor type 2 (HER2)-negative metastatic breast cancer [8]. Patients were randomized into the POC group and the control group in a 1:1 ratio (strati ed, based on the center, use of bone-modifying agents, patient's age, and history of receiving chemotherapy within 3 months).…”
Section: Based On An Evidence Level Of 3 the Mucositis Study Group Omentioning
confidence: 99%
“…Patients were randomly assigned in a 1:1 ratio (strati ed according to center, use of BMA, age, and history of receiving chemotherapy within 3 months) [9]. Eligible patients were enrolled at 31 investigation sites from academic and community settings in Japan on the basis of the following key inclusion criteria: postmenopausal women having histologically or cytologically con rmed metastatic hormone-receptorpositive HER2-negative breast cancer; who were newly prescribed EVE 10 mg and EXE 25 mg; had Eastern Cooperative Oncology Group (ECOG) performance status of 0-1; and showed adequate renal function (serum creatinine level ≤1.5 × upper limit of normal).…”
Section: Methodsmentioning
confidence: 99%
“…Oral Care-BC was a phase 3 multicenter randomized clinical trial that assessed the effectiveness of professional oral care (POC) in preventing oral mucositis in patients treated with EVE and EXE for hormone-receptor-positive HER2-negative metastatic breast cancer. We previously reported that POC reduces the incidence and severity of oral mucositis in patients receiving EVE and EXE and that POC signi cantly reduces the incidence of grade 1 and 2 oral mucositis within 8 weeks [9].…”
Section: Introductionmentioning
confidence: 94%
“…Oral Care-BC was a phase 3 multicenter randomized clinical trial that assessed the effectiveness of professional oral care (POC) in preventing oral mucositis in patients treated with EVE and EXE for hormone-receptor-positive HER2-negative metastatic breast cancer. We previously reported that POC reduces the incidence and severity of oral mucositis in patients receiving EVE and EXE and that POC significantly reduces the incidence of grade 1 and 2 oral mucositis within 8 weeks [9]. However, the population that has a better clinical response among patients receiving EVE and EXE was not established.…”
Section: Introductionmentioning
confidence: 99%